Pengaruh Kualitas Pelayanan dan Kepercayaan Konsumen Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus pada Konsumen Rinni Mekeup Gondang) - Siti Zahrotul Mufidah; Imam Baidlowi; Kasnowo Kasnowo (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to analyze the Effect of Service Quality and Consumer Trust on Customer Loyalty through Customer Satisfaction as an Intervening Variablel. In this study using quantitative data. The method used in data collection is to use questionnaires measured by Likert scale. The sampling technique in this study uses non-probability sampling techniques with a sample of 100 respondents. In this data processing using SmartPLS. The results showed that there is a positive influence of service quality on customer loyalty, there is a positive influence of consumer trust on customer loyalty, there is a positive influence of service quality on customer satisfaction, there is a positive influence of consumer trust on customer satisfaction, there is a positive influence of customer satisfaction on customer loyalty, Service quality hasnot an influence on customer loyalty through customer satisfaction as an intervening variable, consumer trust has an influence on customer loyalty through customer satisfaction as an intervening variable